Response to a strengths-based approach in social work in schools: An Indian school in Dubai. (November 2017) - Pulla, Venkat; Kay, Amanda
Strengths-based approaches in social work have been introduced in the West in a number of social work settings including schools. As part of a research study, the authors investigated the overall reception of students, parents and school counsellors to a strengths-based approach in one-to-one counselling in a school setting. We have utilised a grounded theory approach, allowing the data to drive the research process and the findings to naturally emerge. As a result, the outcomes that unfolded at various stages in our research made us unpack the traditional core expectations of school social work, gaining an insight into the role and expectations of social work roles in a predominantly alien working population living in an Arab country. While the school social work literature is predominantly Western, school social work and its counselling component sit well within the cultures that we grappled with. Despite, this, we have cautiously considered the context of social work and the impacts of the application of strengths-based principles in non-Western environments. Implications for improving student engagement within schools; scope of social work counselling in schools and further research that explores social work methodologies in culturally diverse contexts along with the limitations of this study are discussed in this article.